Ulipristal Acetate Efficacy in a Patient with Symptomatic Fibroid and Concomitant Pulmonary Embolism. (22nd February 2020) - von Wunster, S.; D'Oria, P.; Colonna, L.; Patelli, G.
Abstract : Ulipristal acetate (UPA) is an effective drug for the treatment of symptomatic uterine fibroids. The drug is highly effective in controlling bleeding control and in the recovery of anemia. Here, we report the case of a woman with severe menorrhagia due to a uterine fibroid and with concomitant pulmonary embolism, a serious life-threatening condition. UPA was shown to be effective in reducing fibroid volume and controlling symptoms, without worsening the underlying embolic disease. No adverse events were observed, and the patient has completely recovered.